5G Heterogeneous Networks Self-organizing and Optimization - Rong, Bo; Qiu, Xuesong; Kadoch, Michel; Sun, Songlin; Li, Wenjing (SpringerBriefs in Electrical and Computer Engineering, 2016)
This SpringerBrief provides state-of-the-art technical reviews on self-organizing and optimization in 5G systems. It covers the latest research results from physical-layer channel modeling to software defined network (SDN) architecture. This book focuses on the cutting-edge wireless technologies such as heterogeneous networks (HetNets), self-organizing network (SON), smart low power node (LPN), 3D-MIMO, and more. It will help researchers from both the academic and industrial worlds to better understand the technical momentum of 5G key technologies.